EFFECTIVE WRITTEN COMMUNICATION THROUGH EMAIL: THE DO’S AND DON’TS - Caecillia Devy Kurniawati (Universitas Bandar Lampung, 2022)
Communicating by the use of email is a common thing that takes place for all various purposes, formally and informally. Nonetheless, it becomes challenging for L2 writers to communicate using the written method since it involves a higher level of language proficiency and cognitive level. The complex elements in the language transfer when writing is never seen as just a small issue as it does require its user to be more skillful and advanced. Related to the need of communicating using email, not many are aware of the features and etiquette that could lead them to have a more effective composition when communicating in an email. Undeniably, one of the top requirements in a workplace is for its team to be able to express messages clearly as a part of entrepreneurial skills development. Given this, the study aims at discussing the existing tips for composing effective emails that are adjusted with the modern era, as well as proposing recommendations of the most updated things that should be added or avoided in an effective email. This is a small-scale library study, which is expected to be explored more to be a field study in the future. The recommendations are presented to guide all readers in general, and university-level authorities in particular, to be alert and to keep improving the necessity of writing emails effectively to compete in the global workplace.